Closed Pentaaza[9]helicene and Hexathia[9]/[5]helicene: Oxidative Fusion Reactions of ortho‐Phenylene‐Bridged Cyclic Hexapyrroles and Hexathiophenes. (10th October 2017) - Chen, Fengkun; Tanaka, Takayuki; Hong, Yong Seok; Mori, Tadashi; Kim, Dongho; Osuka, Atsuhiro
Abstract: Oxidative fusion reactions of ortho ‐phenylene‐bridged cyclic hexapyrroles and hexathiophenes furnished novel closed helicenes in a selective manner. X‐Ray diffraction analysis unambiguously revealed the structures to be a closed pentaaza[9]helicene, the longest azahelicene reported so far, and an unexpected double‐helical structure of hexathia[9]/[5]helicene, whose formation was assumed to result from multiple oxidative fusion along with a 1, 2‐aryl shift. The pentaaza[9]helicene exhibited well‐defined emission with high fluorescence quantum yield ( Φ F =0.31) among the known [9]helicenes. Chiral resolution of the racemic pentaaza[9]helicene and hexathia[9]/[5]helicene were achieved by chiral‐phase HPLC and the enantiomers were characterized by circular dichroism spectra and DFT calculations.